The Effects Of Mitragynine On P-Glycoprotein Regulations And Its Neurotoxicity Mechanisms In Brain Cell Lines - Abduraman, Muhammad Asyraf (2021)
The main objective is to determine the effects of mitragynine on P-gp regulations and neurotoxicity effects of drug-herb interactions between mitragynine and P-gp substrates in the PC12 cells using both in silico and in vitro approaches.